Pembuatan Video Tempat-Tempat Angker di Tanjungpinang - Kho, Jensen; Deli, Deli (Computer Based Information System Journal, 2022)
Many things have advanced in today's world as a result of sophisticated technology, one of which is video media. Video is a kind of communication that uses moving images and sound to convey information. The word "video" is derived from the Latin word "vidi" or "visum" which means "to see" or "to have vision." Video media is currently commonly utilized to promote a product or a location that is not well-known, such as promoting haunted locations in a city that is not well-known. Promotion is a marketing strategy used to introduce a product or location with the goal of increasing sales. The R&D approach, which refers to the IDI model, will be used to construct Haunted Place Videography. Haunted sites can have their own allure, particularly for those who enjoy or are intrigued about the supernatural. A haunted location is one that is said to be haunted by spirits and has a mystical story attached to it. This film was created using the information gathered by the researcher. Researchers gathered the information through observations and market research. This design's output or result is a video on Tanjungpinang City's terror spots. The outcomes of this design are expected to aid in the promotion of these destinations as well as dark tourism.